Petrie and Schliemann at the Labyrinth: A Red-Letter Day - Magadán Olives, Maria Teresa (Gerión. Revista de Historia Antigua, 2022)
Flinders Petrie and Heinrich Schliemann, the founding fathers of the Egyptian and Greek archaeology, had many traits in common during their lifetime, but never met each other until April 1888 during Petrie’s excavations at Hawara. Schliemann, who was travelling into Egypt for his fourth and last time, made a tour to visit the place. In the article we reconstruct the meeting taking into account the data preserved and use it to demonstrate Schliemann’s new attitude to archaeology in the last years of his life.